2021
DOI: 10.1073/pnas.2012937118
|View full text |Cite
|
Sign up to set email alerts
|

Learning to silence saccadic suppression

Abstract: Perceptual stability is facilitated by a decrease in visual sensitivity during rapid eye movements, called saccadic suppression. While a large body of evidence demonstrates that saccadic programming is plastic, little is known about whether the perceptual consequences of saccades can be modified. Here, we demonstrate that saccadic suppression is attenuated during learning on a standard visual detection-in-noise task, to the point that it is effectively silenced. Across a period of 7 days, 44 participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 117 publications
(132 reference statements)
2
10
0
Order By: Relevance
“…Thus, visual information that is not consciously accessible during a saccade is not discarded pre-emptively and could be exploited. For example, saccadic suppression associated with microsaccades 104 is reduced when stimuli are presented predictably during saccade execution (Fig. 2d), suggesting that task demands might override saccadic suppression with training 104 .…”
Section: Using Incidental Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, visual information that is not consciously accessible during a saccade is not discarded pre-emptively and could be exploited. For example, saccadic suppression associated with microsaccades 104 is reduced when stimuli are presented predictably during saccade execution (Fig. 2d), suggesting that task demands might override saccadic suppression with training 104 .…”
Section: Using Incidental Consequencesmentioning
confidence: 99%
“…For example, saccadic suppression associated with microsaccades 104 is reduced when stimuli are presented predictably during saccade execution (Fig. 2d), suggesting that task demands might override saccadic suppression with training 104 . Suppression could also dissipate if saccade-induced sensory consequences (such as incidental retinal motion) are reliably absent, such that their dedicated suppression becomes irrelevant 103 .…”
Section: Using Incidental Consequencesmentioning
confidence: 99%
“…Indeed, experimental work has shown that even as early as in the V1 "eye tracker" information can be extracted from neural signals to accurately reconstruct the direction and gaze and, therefore, the location of objects in a craniocentric reference frame [64]. Further, psychophysical experiments have confirmed that visual information is not gated away at PLOS COMPUTATIONAL BIOLOGY specific layers in visual streams but remains available to perceptually relevant visual circuits, for example, permitting learning-mediated improvements of perceptual judgements during saccades [102,115].…”
Section: Shift-vector Information In Movement Signalsmentioning
confidence: 99%
“…However, sensory input inhibition is incomplete. With training, suppression can be dampened if stimulus presentation during a saccade is task relevant [133,134]. Indeed, moving task-relevant stimuli during saccade flight can be detected and used to support post-saccadic gaze correction [135].…”
Section: Box 1 Perceptual Gaps Caused By Saccadic Eye Movementsmentioning
confidence: 99%